1976
DOI: 10.1099/00221287-95-2-297
|View full text |Cite
|
Sign up to set email alerts
|

The Apparent ATP Requirement for Nitrogen Fixation in Growing Klebsiella pneumoniae

Abstract: SUMMARYThe apparent ATP requirement for N, fixation in Klebsiella pneumoniae was high (the ATPIN, molar ratio was 29 when estimated in anaerobic glucose-limited chemostat cultures) compared with that determined previously in Azotobacter chroococcum and in Clostridium pasteurianum. The high value was probably not due to unfavourable temperature, phosphate concentration or pH. The apparent ATP requirement for N, fixation was probably no lower in 0,-limited chemostat cultures than in anaerobic glucose-limited che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…It was also found that the unc+ and uncB-hybrids grew anaerobically to the same extent as each other in NFM, although the growth yield was about 55 % less than in NFM with excess ammonium (Fig. 3) (Hill 1976). When log-phase cultures of AN283(FN68) growing…”
Section: Source Of Atp For Phenotypic Expression Ofnif+ Kp Genes In Ementioning
confidence: 96%
See 3 more Smart Citations
“…It was also found that the unc+ and uncB-hybrids grew anaerobically to the same extent as each other in NFM, although the growth yield was about 55 % less than in NFM with excess ammonium (Fig. 3) (Hill 1976). When log-phase cultures of AN283(FN68) growing…”
Section: Source Of Atp For Phenotypic Expression Ofnif+ Kp Genes In Ementioning
confidence: 96%
“…C Assuming 2·9 mol ATP used per mol glucose (Hadjipetrou et al 1964;Hill 1976). Assuming that the energy requirements for maintenance in the nitrogen-fixing and ammonia-assimilating cells are similar (HilI 1976), then the difference between the two values for ATP molecules available (i.e. 37) will be the number required for fixation of N2.…”
Section: (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, an excess of component I leads to a higher ratio of ATP to electrons transferred (127). In vivo, a constant ratio of these two components is maintained by having the three structural genes (in K. pneumoniae, at least) being part of a single operon, nifHDK (134,142 (97) and 20 ATPs are required in C. pasteurianum (49). The relationship between NH4' formation and carbon substrate used was studied with a derepressed mutant of K. pneumoniae that was not able to assimilate the NH4' produced by N2 fixation (4).…”
Section: Biochemistry Nitrogenasementioning
confidence: 99%